URGENSI MEMASUKKAN MATERI EKONOMI PERTAHANAN DALAM PENGEMBANGAN PEMBELAJARAN EKONOMI DI ERA REVOLUSI INDUSTRI 4.0 - Tri Susdarwono, Endro (CV. Amerta Media, 2019)
Defense Economy is a branch of science that applies economics to national defense problems. The defense economy as a multidisciplinary study addresses the allocation of resources, income distribution, economic growth, and political stability applied to topics related to defense. The results of defense activities are pure public goods, because they are non-exclusive and nonvalidity, so the provision is made by the state. In the provision of defense products, the state must do it effectively and efficiently. This is due to the limited national resources owned by the state, and many other objectives that must be met by the state, such as education, health, and infrastructure development services while on the other hand the defense is always faced with the doctrine of Si Vis Pacem the Bellum. This consideration is the basis of the urgency to include economic defense material in economic learning in the era of industrial revolution 4.0.Key Words: defense economy, economic learning, industrial revolution 4.0.